Exercise-induced BDNF signaling mediates neuroplasticity in depression - Turzyńska, Paulina Patrycja; Liedtke, Marcjanna Maria; Biskup , Alicja; Wnęk , Agata; Martynowska , Weronika; Misiaszek, Dastin; Grabowska, Natalia; Wolszczak, Anna (Quality in Sport, 2026)
Background. Major depressive disorder (MDD) is increasingly recognized as a disorder of impaired neuroplasticity. Brain-derived neurotrophic factor (BDNF) plays a central role in neuronal survival, synaptic plasticity, and antidepressant mechanisms [1–4]. Physical exercise has emerged as an effective non-pharmacological intervention capable of enhancing BDNF signaling and promoting neuroplastic adaptations [20–27]. Aim. To summarize current evidence on the role of exercise-induced BDNF signaling in mediating neuroplastic adaptations and antidepressant effects in depression. Material and methods. A narrative review of peer-reviewed studies, including mechanistic research, randomized controlled trials, cohort studies, and meta-analyses, was conducted. Evidence from neuroscience, exercise physiology, and clinical psychiatry was integrated. Results. Exercise increases BDNF expression through multiple biological pathways, including lactate signaling, muscle–brain crosstalk, and kynurenine metabolism [8–10]. These adaptations promote neurogenesis, synaptic plasticity, and improvements in brain connectivity [11,12,16,17]. Meta-analyses demonstrate that exercise increases circulating BDNF levels and reduces depressive symptoms [14,15,22]. Epidemiological and clinical studies indicate that higher physical activity is associated with a lower risk of depression and improved mental health outcomes [20–30]. Conclusions. BDNF appears to be a key mediator of the antidepressant effects of exercise. Current evidence supports the inclusion of structured physical activity as an evidence-based component of depression treatment, although further research is needed to optimize exercise protocols and clarify individual differences in BDNF responsiveness.